"They Labeled Me Ignorant": Narratives of Maltese Youth With Dyslexia on National Examinations. (June 2019) - Camilleri, Stephen; Chetcuti, Deborah; Falzon, Ruth
Examinations have a significant impact on well-being as they provide qualifications for entry into further education and employment. Research suggests that students with dyslexia experience greater challenges than their counterparts. This article explored the views of eight students with dyslexia, the challenges they face, and what they believe could make national examinations "fairer." The Maltese educational system has a Secondary Education Certificate (SEC) at the end of compulsory education (16 years) and Matriculation (MATSEC) for postsecondary schooling (18 years). Narrative interviews and a thematic approach using discourse analysis presented participants' voices in prose and strophes. Narratives evidence difficulties and abilities. Students criticized the unnecessary examination stress and anxiety caused by misunderstanding and lack of knowledge about dyslexia. Youth referred to "fairness" of examinations, which they equated with "sameness." They believe that examinations could be fairer by being given compensatory measures without compromising the examinations' objectives.